Pelaksanaan Tugas Hakim Pengawas dan Pengamat Pengadilan Negeri Yogyakarta bagi Narapidana Penjara di Lapas Wirogunan dan Lapas Narkotika - Asep Ilham Taufiq (UIN Sunan Kalijaga Yogyakarta, 2016)
The results showed that the implementation of the supervision and observation of some notexercised pursuant to Article 277-283 of Law No. 8 of 1981 on the Law of Criminal ProcedureCode (Criminal Code) and SEMA No. 7 of 1985 regarding Implementation Guidelines tasksSupervisory Judge and Observer, as well as with the provision that the exclusion of JudgeWASMAT in ketentua Act No. 12 of 1995 concerning Corrections, making Judge WASMATless performance. The pattern of coordination and support between law enforcement partners in theimplementation of the Yogyakarta District Court was minimal, forms of cooperation between theagencies in implementing the mandate to be not optimal and there has been no implementation of therules governing the monitoring mechanism on sanctions rehabilitation. The Supreme Court as thejudiciary function organizes the judicial authorities with the aim of enforcing the law and justiceshould immediately issue a policy that can be used as a legal basis for Judge supervisors and observers(WASMAT) in carrying out the supervision of the enforcement of rehabilitation, not to tendarrangement only serves to verdict judge to imprisonment only.